2007
DOI: 10.1186/1472-6955-6-5
|View full text |Cite
|
Sign up to set email alerts
|

Nurses using physical restraints: Are the accused also the victims? – A study using focus group interviews

Abstract: BackgroundTo date, the literature has provided an abundance of evidence on the adverse outcomes of restraint use on patients. Reportedly, nurses are often the personnel who initiate restraint use and attribute its use to ensuring the safety of the restrained and the others. A clinical trial using staff education and administrative input as the key components of a restraint reduction program was conducted in a rehabilitation setting to examine whether there were any significant differences in the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 28 publications
1
37
0
1
Order By: Relevance
“…The review yielded 23 articles that represented one mixed methods (Strumpf & Evans, ), seven quantitative (Farina‐Lopez, Estevez‐Guerra, Polo‐Luque, Pogranyiva, & Penelo, ; Janelli, Stamps, & Delles, ; Liukkonen & Laitinen, ; McCabe, Alvarez, McNulty, & Fitzpatrick, ; Myers, Nikoletti, & Hill, ; Suen et al, ; Werner, ) and 15 qualitative studies (Bok, Pierce, Gies, & Steiner, ; Boltz, Capezuti, & Shabbat, ; Brown, Williams, Woodby, Davis, & Allman, ; Chuang & Huang, ; Dahlke, Hall, & Baumbusch, ; Dahlke & Phinney, ; Goethals, Dierckx de Casterlé, & Gastmans, ; King, Pecanac, Krupp, Liebzeit, & Mahoney, ; Kneafsey, Clifford, & Greenfield, ; Lai, ; Lee, Chan, Tam, & Yeung, ; Ludwick, O'Toole, & Meehan, ; Nolan, ; Quinn, ; Schofield, Tolson, & Fleming, ). Nine were conducted in the United States, three in the United Kingdom, three in Hong Kong, two in Canada and one each in Spain, Taiwan, Belgium, Finland, Australia and Israel.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The review yielded 23 articles that represented one mixed methods (Strumpf & Evans, ), seven quantitative (Farina‐Lopez, Estevez‐Guerra, Polo‐Luque, Pogranyiva, & Penelo, ; Janelli, Stamps, & Delles, ; Liukkonen & Laitinen, ; McCabe, Alvarez, McNulty, & Fitzpatrick, ; Myers, Nikoletti, & Hill, ; Suen et al, ; Werner, ) and 15 qualitative studies (Bok, Pierce, Gies, & Steiner, ; Boltz, Capezuti, & Shabbat, ; Brown, Williams, Woodby, Davis, & Allman, ; Chuang & Huang, ; Dahlke, Hall, & Baumbusch, ; Dahlke & Phinney, ; Goethals, Dierckx de Casterlé, & Gastmans, ; King, Pecanac, Krupp, Liebzeit, & Mahoney, ; Kneafsey, Clifford, & Greenfield, ; Lai, ; Lee, Chan, Tam, & Yeung, ; Ludwick, O'Toole, & Meehan, ; Nolan, ; Quinn, ; Schofield, Tolson, & Fleming, ). Nine were conducted in the United States, three in the United Kingdom, three in Hong Kong, two in Canada and one each in Spain, Taiwan, Belgium, Finland, Australia and Israel.…”
Section: Resultsmentioning
confidence: 99%
“…In 2 of the studies, nursing staff in the United States (US) (Janelli et al, ) and the United Kingdom (UK) (Schofield et al, ) discussed using chemical restraints to keep their older patients from harms that were defined as falling or removing medical equipment (e.g., catheters, intravenous lines). Studies from Taiwan (Chuang & Huang, ), Spain (Farina‐Lopez et al, ), the United States (King et al, ; Ludwick et al, ; McCabe et al, ; Quinn, ; Strumpf & Evans, ), Hong Kong (Lai, ; Lee et al, ; Suen et al, ), Finland (Liukkonen & Laitinen, ), Australia (Myers et al, ) and Israel (Werner, ) all reported nurses' use of physical restraints to keep their older patients safe. Four of the studies identified that once physical restraints had been applied to an older patient, nursing teams were reticent to remove them, even if the reason for using the restraint was no longer present (Chuang & Huang, ; Goethals et al, ; Ludwick et al, ; Suen et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some organisational factors might influence the rate of physical restraint use, knowledge and attitude of nurses are ultimately the most powerful determinants of restraint use (Feng et al., ; Suen et al., ). Several studies demonstrated that nurses’ knowledge towards physical restraint was inadequate (Kandeel & Attia, ; Suen et al., ) and their attitudes were negative or they had ambivalent feelings regarding the physical restraints (Huang, Chuang, & Chiang, ; Lai, ; Mohler & Meyer, ). Thus, the study by Wynn () demonstrated that most nurses do not believe that more restlessness, aggression and injury could be a result of using physical restraints in hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of knowledge related to proper use, several studies have found that nurses' knowledge failed to attain a satisfactory level (Hsu, Huang, & Chen, 2006;Huang et al, 2003;Karlsson, Bucht, & Sandman, 1998;Suen et al, 2006;Swauger & Tomlin, 2001). In addition, it is evident that some nurses have ambivalent attitudes regarding physical restraint use (Chuang & Huang, 2007;Lai, 2007;Lee, Chan, Tam, & Yeung, 1999). Some nurses favored the use of physical restraints (Chang et al, 2006;Myers et al, 2001), whereas others held negative attitudes (Huang et al, 2003;Suen et al, 2006), and some had mixed feelings (Lee et al, 1999).…”
mentioning
confidence: 99%